Recent nanofabrication of silicon dioxide on silicon wafer using AFM operated at low temperature - Sutjipto, Agus Geter Edy; , Afzeri; Shafie, Amir Akramin (Trans Tech Publications Ltd., Switzerland, 2011)
Field-induced oxidation has become a promising process that is capable of directly producing high-resolution surface oxide patterns on variety materials. This report initiated the idea of the possibility of a controlled nanofabrication of SiO2 on silicon wafer by utilizing a frozen humid air film. A low temperature (-70oC) operation of an atomic force microscope (AFM) was used to condense ambient humidity (40%) to perform a thin frozen water layer covering a silicon wafer surface. A scanning probe was contacted with the layer and a zero bias voltage was applied to the sample surface with the AFM probe tip connected to the reference -2.44V. The frozen water film acted both as an electrolyte to form silicon dioxide and as a resource of hydroxide. Using this technique (a) a consistency in height of 6 nm silicon dioxide patterns layer could be achieved showing that the effect of tip vibration could be reduced; (b) easy to remove frozen water by just operating the AFM to the ambient temperature; (c) it is possible to control thickness by making different humidity.